THE EFFECT OF EMOTIONAL INTELLIGENCE AND INDEPENDENCE IN LEARNING ON MATHEMATICS LEARNING OUTCOMES TO FIFTH GRADE STUDENTS OF PUBLIC ELEMENTARY SCHOOLS IN NGOMBOL SUB-DISTRICT IN ACADEMIC YEAR OF 2020/2021 - Lutfia Islahati; Rokhmaniyah Rokhmaniyah; Ngatman Ngatman (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2021)
The study aimed to determine emotional intelligence and independence in learning on mathematics learning outcomes to fifth grade students of public elementary schools in Ngombol Sub-district in academic year of 2020/2021. It was correlational quantitative method. The prerequisite test used linearity, normality, and multicolinearity tests. The data analysis used regression test and correlation test with a significance level of 5%. It concludes that there is positive and significant effect of emotional intelligence and independence in learning on mathematics learning outcomes to fifth grade students of public elementary schools in Ngombol Sub-district in academic year of 2020/2021. The emotional intelligence and learning independence contribute 19.3% on mathematics learning outcomes and the remaining 80.7% was influenced by other factors.